2010
DOI: 10.1007/s11671-010-9666-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Extinction and Visible Transparency by Ivy Nanoparticles

Abstract: Though much research has been conducted for nanoparticles, naturally occurring nanoparticles have not yet been well explored for their diverse properties and potential applications. This paper reports the optical absorption and scattering properties of nanoparticles secreted by English ivy. Both experimental and theoretical studies have been conducted. Strong ultraviolet extinction and excellent visible transparency are observed, compared to the inorganic TiO2 and ZnO nanoparticles at similar concentrations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…These peaks were positively correlated with the AFM and DLS data, and confirmed the presence of the ivy nanoparticles. In previous studies, determination of the concentration of ivy nanoparticles in solution could only be estimated, owing to the limited quantity of nanoparticles [6]. Using the method developed above, after collecting the concentrated ivy nanoparticles, the samples were pooled and lyophilized to get an accurate measure of the dry weight of the ivy nanoparticles.…”
Section: Rsifroyalsocietypublishingorg J R Soc Interface 10: 20130392mentioning
confidence: 99%
See 3 more Smart Citations
“…These peaks were positively correlated with the AFM and DLS data, and confirmed the presence of the ivy nanoparticles. In previous studies, determination of the concentration of ivy nanoparticles in solution could only be estimated, owing to the limited quantity of nanoparticles [6]. Using the method developed above, after collecting the concentrated ivy nanoparticles, the samples were pooled and lyophilized to get an accurate measure of the dry weight of the ivy nanoparticles.…”
Section: Rsifroyalsocietypublishingorg J R Soc Interface 10: 20130392mentioning
confidence: 99%
“…Using the method developed above, after collecting the concentrated ivy nanoparticles, the samples were pooled and lyophilized to get an accurate measure of the dry weight of the ivy nanoparticles. To confirm that the previously observed UV/vis absorbance spectra [6,7] were due to the ivy nanoparticles alone, it was necessary to analyse the concentration-dependent effect of the ivy nanoparticles using UV/vis spectroscopy. As shown in figure 4a, when the concentration of the ivy nanoparticles decreased, the resulting absorbance decreased.…”
Section: Rsifroyalsocietypublishingorg J R Soc Interface 10: 20130392mentioning
confidence: 99%
See 2 more Smart Citations
“…1) were secreted in the adhesive of English ivy and played an important role in generating the adhesive force necessary for the plant to climb near vertical surfaces [11]. Further studies with the ivy nanoparticles demonstrated an increased UV protective effect when compared to T i O 2 or Z n O nanoparticle fillers commonly used in sunscreens, indicating potential applications for the ivy nanoparticle sunscreen additives [12], [13]. Further analysis showed that at similar concentrations, ivy nanoparticles were nontoxic, when compared to T i O 2 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%